Performance of European Industry of Logistics Services Before and AfterEconomic Crises in the Years 2008/2009 (Journal of Universal Excellence, 2026)
Research question: The basic research question is: Were implications of economic crises in the years 2008/2009 in logistics industry in heterogenic states of European Union; old member states EU-15 and the new EU member states different?Purpose:We wanted to determine how the logistics companys in old member States EU (15) and in the new EU member states adapt to the new circumstances caused by economic crises in the years 2008/2009.Method: Economic crises are complex multifunctional phenomenon. Analysing complexity of the changes of the state of economic system need to supplement the pure scientific approach with other types of research work, more holistic approach, which is commonly used in Comparative economics. In this article we combine both. In empirical part we used appropriate parametric and non-parametric tests of differences between old and new member states of the European Union. We used Pearson's chi-squared test (Pearson, 1900, p. 157-175).Results: In the article we studied changes ocured by economic crises in the years 2008/2009 in the European logistics industry. We found that the logistics companies in the old EU member states EU-15 and in the new EU member states differently adapt to the implications of economic crises in the years 2008/2009. EU hasn’t adopted and implemented the harmonised economic policy, which will solve the »North-South« problem in logistics industry and find a way to operate systemically in global environment.Organization: The findings can be used to support undestanding of changed bussines envirnment of the logistics companies and contribute for better strategic planning and design of the entire supply chain.Society: The findings can contribute to better understanding of  economic crises 2008/2009 in the European logistics industry and integrative processes in the European Union.Originality: We examined the implications of crises in the years 2008/2009, relating to the determination of changed values of certain economic parameters in the segment of road freight transport in National Economies of EU Member States, from the perspective that so far nobody has yet addressed.Limitations/Future research: The complexity of the problem as economic crises is complex multifunctional phenomenon and the dynamic changes in the functioning of the european logistics market requires in-depth studiying of changes in the micro and macro environment of logistics companies.
Keywords: economic crises; European Union; EU-15; Central and Southeastern Europe; logistics; transport; effectiveness; efficiency